Assimilation via Prices or Quantities? Sources of Immigrant Earnings Growth in Australia, Canada and the United States - Heather Antecol; Peter Kuhn; Stephen Trejo (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
Using 1980/81 and 1990/91 census data from Australia, Canada, and the United States, we estimate the effects of time in the destination country on male immigrants' wages, employment, and earnings. We find that total earnings assimilation is greatest in the United States and least in Australia. Employment assimilation explains all of the earnings progress experienced by Australian immigrants, whereas wage assimilation plays the dominant role in the United States, and Canada falls in-between. We argue that relatively inflexible wages and generous unemployment insurance in countries like Australia may cause assimilation to occur along the "quantity" rather than the price dimension.
Keywords: 330